2007
DOI: 10.1007/s10495-007-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

ROS production by adrenodoxin does not cause apoptosis in fission yeast

Abstract: We previously showed that production of reactive oxygen species (ROS) caused by overexpression of the mitochondrial electron transfer protein adrenodoxin (Adx) induces apoptosis in mammalian cells. In the fission yeast Schizosaccharomyces pombe, ROS are also produced in cells that undergo an apoptotic-like cell death, but it is not yet clear whether they are actually causative for this phenomenon or whether they are merely produced as a by-product. Therefore, the purpose of this study was to trigger mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…31 Similar studies have shown that ROS are also produced in cells undergoing apoptotic-like cell death, but that the produced ROS do not cause apoptosis. 32 In this study, we observed that ROS were not required to induce apoptosis in PTEN-proficient glioma.…”
Section: Discussionmentioning
confidence: 61%
“…31 Similar studies have shown that ROS are also produced in cells undergoing apoptotic-like cell death, but that the produced ROS do not cause apoptosis. 32 In this study, we observed that ROS were not required to induce apoptosis in PTEN-proficient glioma.…”
Section: Discussionmentioning
confidence: 61%
“…ROS may also serve as cell signaling molecules and cause damage to foreign bodies (37). Overproduction of ROS may be induced by a number of intra-and extracellular stressors (38)(39)(40). In the present study, the production of ROS in Aloin-treated A549 cells was evaluated.…”
Section: Discussionmentioning
confidence: 94%
“… 103 Interestingly, recombinant expression of Adx does not cause apoptosis in the microbial model system Schizosaccharomyces pombe , in spite of a strong increase in ROS, which is indeed much higher than that observed in mammalian cells. 114 An explanation for this observation might well be connected to the very recent finding that S. pombe , in contrast to baker’s yeast ( Saccharomyces cerevisiae ), does not age. 115 …”
Section: Cytochrome P450 Enzymesmentioning
confidence: 99%